Role of bronchoscopy during non invasive ventilation in hypercapnic respiratory failure - W. Rady; A. Abouelela; A. Abdallah; W. Youssef (Egyptian Journal of Chest Disease and Tuberculosis, 2014)
Introduction: Non invasive positive pressure ventilation (NIPPV) is the first line treatment for hypercapnic acute respiratory failure (ARF) secondary to COPD exacerbation in selected patients. Limited data exist supporting the use of fiberoptic bronchoscopy (FOB) during this clinical setting. The aim of this study is to assess the role of FOB during NIPPV in patients with decompensated COPD acute exacerbation. Methods: This study is a randomized prospective case control pilot study carried out on 50 patients - admitted to critical care units at Alexandria University Hospital, Egypt - suffering from hypercapnic ARF secondary to COPD exacerbation with Kelly Matthay Score from 2 to 4. All patients received NIPPV. Patients were divided randomly into 2 equal groups: group I (cases) (25 patients) was subjected to additional intervention of early FOB during the first 6–12 h from admission while group II (control) (25 patients) received the conventional treatment and NIPPV only. Outcome parameters measured were changes in ABG data, duration of NIPPV, rate of its success, ICU stay and mortality as well as the safety of FOB and possible complications. Results: No significant difference was detected between the 2 groups regarding the baseline characteristics. No serious complications happened from FOB, and Oxygen desaturation happened in 4/25 patients (16%), Tachycardia in 2/25 patients (8%). In group I, 23 patients (92%) were successfully weaned from NIPPV versus 16 patients (64%) in group II (p = 0.037). Total duration of NIPPV was 28.52 h in group I versus 56.25 h in group II (p = 0.001). Length of ICU stay was 4.84 days in group I versus 8.68 days in group II (p = 0.001). Only 1 patient died in group I versus 3 patients in group II (p = 0.609). Conclusion: The early application of FOB during NIPPV in patients with ARF due to COPD exacerbation was shown to be safe. Significant improvement in the outcome of patients who underwent FOB was noticed in terms of improved ABG data, shorter duration of NIPPV, higher percentage of success and shorter ICU stay while no significant difference was detected in mortality.